Additive manufacture of dissolvable tooling for autoclave processing of fiber reinforced polymer composites - Morris, Isaac, author; Radford, Donald, advisor; Yourdkhani, Mostafa, committee member; Heyliger, Paul, committee member (Colorado State University. Libraries, 2022)
Autoclave processing of advanced fiber reinforced polymer composites (AFRPC) uses applied heat and pressure to yield high quality composite components. Geometrically accurate and thermally stable molds or tools are used to maintain the part form until the part cures and rigidizes. For high-volume production runs, molds may be made from materials such as metals, ceramics, or AFRPCs. However, tooling made from these materials can be costly to manufacture and are not suitable for low volume production runs. This is especially true for complex geometries in trapped tooling situations where the cured composite shape prevents tool separation. In this situation, composite manufacturers rely on sacrificial washout tooling materials that are machined or cast to shape to create the tool. However, these sacrificial materials still come with significant challenges. For example, the surfaces of these tools are often porous and require sealing, and their washout can result in corrosive waste that makes disposal challenging. Additionally, these tools are brittle and monolithic in nature, making them fragile to handle and slow to heat up during cure. An alternative may be to use high temperature, dissolvable thermoplastic materials in melt extrusion additive manufacturing to create complex washout tooling. However, there is a lack of information regarding the types of soluble materials and the structural configurations that make this type of tooling successful in autoclave use. To begin to address this, samples made from several materials, and one insoluble model material, were processed in stepwise fashion at increasing autoclave processing temperatures to evaluate the impacts of material and structure on autoclave robustness. Then, mid-sized composite specimens were produced on 3D-printed tooling that evaluated the interaction between the composite and the tool, including surface quality and deformation. Finally, a trapped tooling geometry was used to manufacture several composites at processing conditions of 157°C at 414kPa, well above the use temperature of the tested materials. These trials focused on reducing deformation by adjusting the tool wall thickness and vacuum bagging configuration. It was shown that 3D-printed dissolvable tooling can be used as an alternative to traditional washout tooling for autoclave processing. The materials Stratasys ST-130 and Infinite Material Solutions AquaSys 180 were used to manufacture tools that were processed at autoclave conditions of 121°C at 345kPa with minimal deformation. Surface quality was also found to be acceptable without machining or sealing, eliminating this step from the production of traditional washout tools. Finally, a modified tool design and vacuum bagging technique were demonstrated that significantly reduced the deformation of tooling at processing temperatures that significantly exceed the use temperature of the material.